Efficacy of two hemodialyses in patients with chronic renal failure complicated by massive intracerebral hemorrhage - Xiangyu Zhu; Qiu Han; Lei Xia; Jin Shang; Xianliang Yan (Annals of Clinical and Translational Neurology, 2023)
Abstract Objective To compare the efficacy of intermittent hemodialysis (IHD) and continuous veno‐venous hemofiltration (CVVH) in patients with chronic renal failure complicated by massive intracerebral hemorrhage. Methods Sixty‐two patients were randomly and equally divided into IHD and CVVH groups. The clinical variables were compared, including National Institutes of Health Stroke Scale (NIHSS) score as the primary indicator, cerebral edema volume, hospital‐acquired pneumonia (HAP) incidence, acute heart failure (AHF) incidence, rehemorrhage incidence, hospital stay length, and modified Rankin Scale (mRS) score. Results The CVVH group had lower NIHSS scores and edema volumes than the IHD group on postoperative days 7 and 14. Moreover, in the CVVH group, (i) the NIHSS scores on postoperative days 3 and 7 were higher than those on postoperative day 1; (ii) there was no significant difference in NIHSS scores between days 14 and 1; and (iii) no significant difference in cerebral edema volume was found between postoperative days 1 and 3, 7, and 14. In the IHD group, the NIHSS scores and cerebral edema volume on postoperative days 7 and 14 were significantly higher than those on postoperative day 1. The CVVH group had a lower incidence of HAP, AHF, and adverse events and shorter hospital stay length than the IHD group. The proportions of patients with mRS scores of 1 and 2 in the CVVH group were higher than those in the IHD group on day 30 after discharge. Interpretation CVVH is more effective than IHD in the treatment of patients with chronic renal failure complicated by massive intracerebral hemorrhage.